Beyond the walls : new perspectives on the archaeology of historical households (University Press of Florida, 2016)
While household archaeologists view the home as a social unit, few move their investigations 'beyond the walls' when contextualising a household in its community. This innovative volume examines historical homes and their wider landscapes to more fully address social issues of the past.